Frozen mummies from Andean mountaintop shrines: bioarchaeology and ethnohistory of Inca human sacrifice - Ceruti, Maria Constanza (2015)
This study will focus on frozen mummies of sacrificial victims from mounts Llullaillaco (6739 m), Quehuar (6130 m), El Toro (6160 m), and the Aconcagua massif. These finds provide bioarchaeological data from mountaintop sites that has been recovered in scientifically controlled excavations in the northwest of Argentina, which was once part of the southern province of the Inca Empire. Numerous interdisciplinary studies have been conducted on the Llullaillaco mummies, including radiological evaluations by conventional X-rays and CT scans, which provided information about condition and pathology of the bones and internal organ, as well as dental studies oriented to the estimation of the ages of the three children at the time of death. Ancient DNA studies and hair analysis were also performed in cooperation with the George Mason University, the University of Bradford, and the Laboratory of Biological Anthropology at the University of Copenhagen. Ethnohistorical sources reveal interesting aspects related to the commemorative, expiatory, propitiatory, and dedicatory aspects of human sacrifice performed under Inca rule. The selection of the victims along with the procedures followed during the performance of the capacocha ceremony will be discussed, based on the bioarchaeological evidences from frozen mummies and the accounts recorded by the Spanish chroniclers.